PENTINGNYA PEMANTAUAN KESEHATAN HUTAN DALAM PENGELOLAAN HUTAN KEMASYARAKATAN - Fansuri Fikri Haikal; Arief Darmawan; Hari Kaskoyo; Rahmat Safe'i (JURNAL HUTAN PULAU-PULAU KECIL, 2020)
Community forestry is a social forestry scheme in state forests. Hkm empowers communities around the forest area to increase the ability and independence of the local community. Forest health monitoring is still rarely applied in the management of HKm. Forest health monitoring results can be a reference in making the right decisions in managing HKm so that the results obtained can be optimal. This study aims to determine the results of forest health monitoring in Beringin Jaya HKm managed by KTH Lestari Jaya 8. The research was conducted using the Forest Health Monitoring (FHM) method. Forest health monitoring results show that there are 6 cluster plots with the final value of forest health status in cluster 1 (2.53) bad category, plot 2 (8.98) good category, plot 3 (6.31) moderate category, plot cluster 4 (10.51) category is good, cluster plot 5 (10.74) category is good and cluster plot 6 (8.98) category is good. Thus the results of forest health monitoring obtained by KTH Lestari Jaya 8 with an average final value of forest health status is moderate